2018
DOI: 10.1016/j.semcancer.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Role of Forkhead Box Class O proteins in cancer progression and metastasis

Abstract: It is now widely accepted that several gene alterations including transcription factors are critically involved in cancer progression and metastasis. Forkhead Box Class O proteins (FoxOs) including FoxO1/FKHR, FoxO3/FKHRL1, FoxO4/AFX and FoxO6 transcription factors are known to play key roles in proliferation, apoptosis, metastasis, cell metabolism, aging and cancer biology through their phosphorylation, ubiquitination, acetylation and methylation. Though FoxOs are proved to be mainly regulated by upstream pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 173 publications
4
81
0
Order By: Relevance
“…FoxOs are well‐known downstream effectors of the PI3K/AKT signaling . RNA sequencing also revealed that FoxO6 was one of the top decreased molecules in HCC cells with 5‐HT1D knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…FoxOs are well‐known downstream effectors of the PI3K/AKT signaling . RNA sequencing also revealed that FoxO6 was one of the top decreased molecules in HCC cells with 5‐HT1D knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory role of the PI3K/Akt pathway in cancer development has received much attention. Foxo1 is a nuclear transcription protein with highly conserved DNA binding sites, and is the substrate of PI3K/Akt, which plays a negative role in insulin signal transduction . Foxo1 is well known to mediate apoptosis by activating the proapoptotic genes, such as FasL and Bim .…”
Section: Discussionmentioning
confidence: 99%
“…FOXOs are putative tumor suppressors as combined loss of Foxo1, Foxo3, and Foxo4 in adult mice results in increased hematopoietic lineage-specific tumors and FOXO activation arrests the cell cycle and induces apoptosis or anoikis in multiple types of tumor cells (2)(3)(4)(5). Despite their tumor-suppressive roles, mutational loss of all FOXO alleles is statistically unlikely and has not been reported in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that FOXOs may also contribute to tumorigenesis, and a more active mutant form of FOXO1 has been reported in cancer (3,(5)(6)(7)(8)(9)(10). In addition, FOXOs have been implicated in a drug resistance signaling feedback loop that reestablishes RTK-PI3K-AKT signaling after pharmacologic inhibition of AKT/PKB (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%